Motivasi Perataan Penghasilan - Alwan Sri Kustono (The Indonesian Journal of Accounting Research, 2013)
This study was aimed to analyze the effect of some factors towards income smoothing tendency and the influence of the income smoothing tendency towards firm value on non financial public companies at the Indonesia Stock Exchange.  Those factors are debt, independent commissioners, and auditor quality. This study was performed using field research. Data were collected from Indonesian Capital Market Directories.  Sample in this study is 100 non financial firms which listed at the Indonesia Stock Exchange from 1999-2005 and is derived using some criteria. This study used Partial Least Square regression technique.The result showed that income smoothing tendency was positive affected by debt. The findings refused first hypothesis. The findings might be of interest to creditors to make credit decision. The study contributed to the literature in that it has shown that income smoothing practice is driven by opportunistic management motive rather than efficiency. Managers should not exercise it because public did not care the practice.